Strength, Motor Skills, and Physical Activity in Preschool-Aged Children Born Either at Less Than 30 Weeks of Gestation or at Term. Issue 5 (1st February 2021) - FitzGerald, Tara L; Cameron, Kate L; Albesher, Reem A; Mentiplay, Benjamin F; Lee, Katherine J; Clark, Ross A; Cheong, Jeanie L Y; Doyle, Lex W; McGinley, Jennifer L; Spittle, Alicia J
Abstract: Objective: Children born <30 weeks of gestation have more motor impairment than do children born at term (37–42 weeks gestation), but reported outcomes have largely focused on cerebral palsy and developmental coordination disorder. The aim of this study was to compare muscle strength, motor skills, and physical activity (PA) of preschool-aged children born <30 weeks with those born at term. Methods: In this cohort study, 123 children born <30 weeks and 128 born at term were assessed. Children were aged ≥4 years, 0 months and <6 years, 0 months' corrected age at the time of the assessment. Outcomes included grip strength (kg), Movement Assessment Battery for Children 2nd edition (MABC-2), Little Developmental Coordination Disorder Questionnaire, accelerometer-measured PA, and a parent-completed PA diary. Linear regression and mixed effects models were used to examine differences between children born <30 weeks and those born at term. Results: Children born <30 weeks had poorer grip strength (preferred hand; mean difference [95% CI] −0.60 kg [−1.04 to −0.15]) and poorer motor competence (Movement Assessment Battery for Children 2nd edition standard score mean difference −2.17 [−3.07 to −1.27]; Little Developmental Coordination Disorder Questionnaire total score mean difference −5.5 [−9.2 to −2.8]) than term-born children. Children born <30 weeks also completed fewer minutes of accelerometer-measured PA (mean difference −41 minutes [−62 to −20]), more minutes of accelerometer-measured stationary behavior (mean difference 33 minutes [12 to 54]), and more minutes of parent-reported screen time (mean difference 21 minutes [10 to 32]) per day. Conclusion: Preschool-aged children born <30 weeks had poorer muscle strength, motor skills, and PA levels than term-born children. These findings suggest that preschool-aged children born <30 weeks may benefit from enhanced surveillance and PA promotion to improve life-long health outcomes. Impact: In our study, children born <30 weeks had reduced muscle strength and poorer motor skills, participated in less PA, and had more stationary and screen behavior than term-born children. These findings emphasize that awareness of multidomain motor deficits in children born <30 weeks' gestation is needed in clinical practice. Given the associations between higher PA and health benefits and the recognition that PA levels can track from early childhood into adulthood, our study highlights the need for assessment and promotion of PA in preschool-aged children born <30 weeks' gestation. Lay Summary. Preschool-aged children born <30 weeks' gestation have poorer strength, motor skills, and physical activity behaviors than their term-born peers. Clinicians and early childhood educators should recognize that the preschool period is a critical time for the assessment and promotion of PA in children born <30 weeks.